Enhancing students’ content and language development: Implications for researching multilingualism in CLIL classroom context - Tai, Kevin W.H.; Wei, Li; Loh, Elizabeth Ka Yee (Learning and instruction, 2025)
The articles in this special issue of Learning and Instruction emphasize four major research areas that have developed in Content and Language Integrated Learning (CLIL) education: (1) the role of translanguaging practices in CLIL classrooms, (2) the use of technological resources to create a technology-mediated translanguaging space in CLIL classrooms, (3) CLIL teachers’ awareness of the pedagogical philosophies of translanguaging, and (4) the role of translanguaging in designing CLIL assessments. This introduction will start by discussing the articles in this special issue and highlighting important theoretical and methodological themes. It will also examine the implications of using translanguaging as a methodological framework in CLIL research, which would help teachers and researchers to gain a deeper understanding of the meaning-making processes in CLIL classrooms. Additionally, this introduction will offer future research directions on dynamic multilingual practices in CLIL classrooms.